2015
DOI: 10.1007/s11010-015-2585-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of sialic acid levels among some organs during insulin resistance or hyperglycemic states

Abstract: Previous studies have suggested a possible connection between insulin resistance and chronic hyperglycemia with membrane sialic acid content. In this study, the effects of high (20% ad libitum) fructose and glucose feeding on the sialic acid levels of some organs were investigated in rats. The blood glucose levels of the high fructose- and glucose-fed rats were consistently and significantly (P < 0.05) higher than the normal control throughout the experiment. Free serum sialic acid and total hepatic sialic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Although we found decreased tissue SA levels, details on the modulation of SA metabolism between various organs under insulin resistance or chronic hyperglycemic conditions are insufficient. In their experimental study, Ibrahim et al [38] found decreased pancreatic SA levels in high-glucosefed rats when compared to the healthy group, but high fructose and glucose feeding did not affect SA levels in the muscle and heart. In the kidney and liver, they observed significantly increased SA levels in both the high-fructose and glucose feeding groups.…”
Section: Discussionmentioning
confidence: 90%
“…Although we found decreased tissue SA levels, details on the modulation of SA metabolism between various organs under insulin resistance or chronic hyperglycemic conditions are insufficient. In their experimental study, Ibrahim et al [38] found decreased pancreatic SA levels in high-glucosefed rats when compared to the healthy group, but high fructose and glucose feeding did not affect SA levels in the muscle and heart. In the kidney and liver, they observed significantly increased SA levels in both the high-fructose and glucose feeding groups.…”
Section: Discussionmentioning
confidence: 90%
“…In diabetic rat liver, increased expression of monosialogangliosides GM1 and GM3, disialoganglioside GD1b and trisialoganglioside GT1b, with a marked absence of GM2 were found (Sanchez et al, 2000;Abregu et al, 2002). Rats subjected under a high fructose and glucose diet showed elevated sialic acid synthesis in the liver and kidney with concomitant loss of sialic acids in the pancreas (Ibrahim et al, 2016).…”
Section: Sialicmentioning
confidence: 97%
“…Некоторые ингибиторы сиалидазы могут являться глюкозозависимым усилителем секреции инсулина [10]. При алиментарной гипергликемии у крыс наблюдалось повышение содержания СК в сыворотке крови [11].…”
Section: обоснованиеunclassified